Exploring the Photocatalytic and Photovoltaic properties of 2D Materials: A Comprehensive Review - Shehroz Abdullah; Dr.Ghulam Murtaza; Muhammad Awais Jehangir (Dialogue Social Science Review (DSSR), 2025)
Two-dimensional (2D) materials have emerged as highly promising candidates for advanced energy conversion technologies due to their unique optical, electronic, and surface properties. This review presents an in-depth examination of the photocatalytic and photovoltaic potential of various 2D materials, including transition metal chalcogenides (TMDs), MXene, black phosphorus, and layered perovskites. Key material attributes—such as bandgap tunability, light absorption efficiency, and charge carrier behavior—are discussed in relation to their roles in solar energy harvesting and photocatalytic water splitting. The paper further explores recent innovations in heterostructure engineering, surface modification, and material synthesis strategies designed to boost energy conversion performance. Challenges such as long-term material stability, large-scale production, and interfacial optimization are critically assessed. Additionally, the review highlights future research pathways that may help translate laboratory-scale success into practical applications. By integrating findings from both experimental investigations and theoretical modeling, this work aims to provide a well-rounded perspective on the role of 2D materials in next-generation renewable energy solutions.